KUALITAS PRODUK KOMPOS DAN KARAKTERISTIK PROSES PENGOMPOSAN SAMPAH KOTA TANPA PEMILAHAN AWAL - Firman L. Sahwan (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Early sorting process in composting municipal solid waste is labour intensive, so that the production cost is high. This research is carried out to know how the quality of the compost product and the characteristic of composting process if the early sorting is not done. The research result shows that without early sorting composting process has been done well, similar or not different significantly to the process with early sorting and has good quality. The positive result of this research is to increase the efficiency of the worker or reduce the production cost of manufacturing compost, because the process in making heap can increase from 1 m3 / person / day to 3 m3 / person / day. Key Words: Compost, composing,municipal solid waste, sorting